The genetic basis of undiagnosed muscular dystrophies and myopathies: Results from 504 patients. (5th July 2016) - Savarese, Marco; Di Fruscio, Giuseppina; Torella, Annalaura; Fiorillo, Chiara; Magri, Francesca; Fanin, Marina; Ruggiero, Lucia; Ricci, Giulia; Astrea, Guja; Passamano, Luigia; Ruggieri, Alessandra; Ronchi, Dario; et al.
Abstract : Objective: To apply next-generation sequencing (NGS) for the investigation of the genetic basis of undiagnosed muscular dystrophies and myopathies in a very large cohort of patients. Methods: We applied an NGS-based platform named MotorPlex to our diagnostic workflow to test muscle disease genes with a high sensitivity and specificity for small DNA variants. We analyzed 504 undiagnosed patients mostly referred as being affected by limb-girdle muscular dystrophy or congenital myopathy. Results: MotorPlex provided a complete molecular diagnosis in 218 cases (43.3%). A further 160 patients (31.7%) showed as yet unproven candidate variants. Pathogenic variants were found in 47 of 93 genes, and in more than 30% of cases, the phenotype was nonconventional, broadening the spectrum of disease presentation in at least 10 genes. Conclusions: Our large DNA study of patients with undiagnosed myopathy is an example of the ongoing revolution in molecular diagnostics, highlighting the advantages in using NGS as a first-tier approach for heterogeneous genetic conditions.